2011
DOI: 10.1016/j.juro.2010.09.112
|View full text |Cite
|
Sign up to set email alerts
|

Functional Detrusor Myoplasty for Bladder Acontractility: Long-Term Results

Abstract: The results of this multicenter analysis demonstrate that latissimus dorsi detrusor myoplasty is an effective alternative to clean intermittent catheterization in a select group of patients with neurogenic bladder acontractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…If an acontractile bladder is diagnosed and less invasive treatments have failed, more invasive surgical reconstructive procedures have been successfully applied to restore bladder function. Latissimus dorsi muscle transposition has been successfully used by Stenzl et al57 and results of a multicenter study have been described by Gakis et al58 Besides reconstructive procedures, tissue engineered constructs or injected stem cells59 might be considered as an option for restoring the contractile function of the bladder.…”
Section: Resultsmentioning
confidence: 99%
“…If an acontractile bladder is diagnosed and less invasive treatments have failed, more invasive surgical reconstructive procedures have been successfully applied to restore bladder function. Latissimus dorsi muscle transposition has been successfully used by Stenzl et al57 and results of a multicenter study have been described by Gakis et al58 Besides reconstructive procedures, tissue engineered constructs or injected stem cells59 might be considered as an option for restoring the contractile function of the bladder.…”
Section: Resultsmentioning
confidence: 99%
“…10 The results revealed that some degree of bladder contractility was still present in 84% of patients, although micturition parameters such as postvoid residual urine volume were not significantly altered. 10 Thus, one cannot exclude the possibility that a consider able number of patients in our study 9 might have had detrusor hypocontractility rather than acontractility. Taking this into account, it seems reasonable to broaden the indications for LDDM to patients diagnosed with detrusor hypocontractility on conventional urodynamic assessment, who until now would not have been considered candidates.…”
Section: Georgios Gakis Milomir Ninkovic and Arnulf Stenzlmentioning
confidence: 91%
“…But what of the minority of cases with hypocontractile bladder or bladder acontracility? Many of the patients in our study 9 who opted for LDDM had performed CIC for several years and preoperatively reported a reduced quality of life. Over the long term, the integration of CIC into one's daily CORRESPONDENCE Bladder hypocontractility-extending the indication for LDDM…”
mentioning
confidence: 88%
See 2 more Smart Citations